Short term effects of valsartan on portal blood flow in cirrhotic patients - Yalniz, Mehmet (Sociedad Iberoamericana de Informacion Cientifica, 2006)
Background: Lowering the elevated pressure is essential for the treatment and prevention of acute or recurrent variceal hemorrhages in patients with portal hypertension. Although several pharmacological agents have been used with this purpose, there is no ideal drug yet. In this study, short-term effects of valsartan, an angiotensin II receptor antagonist, upon portal blood flow in cirrhotic patients were evaluated. Methods: 36 cirrhotic patients were treated with 80 mg/day valsartan for one week. Effects upon hemodynamic parameters were evaluated by colored Doppler ultrasonography 24 hours prior and then, 4 and 8 days after administration of the drug. Following parameters were evaluated: peak systolic flow velocity, diastolic flow velocity, peak systolic flow velocity/diastolic flow velocity ratio, resistive index and pulsatility index in hepatic, superior mesenteric and right and left renal arteries, and diameter (PVD), mean flow velocity (PVMFV) and flow volume (PVFV) in portal vein. Results: Hemodynamic parameters evaluated in the hepatic, superior mesenteric and right and left renal arteries did not show any significant changes with administration of valsartan. However, a significant decrease in PVD, PVMFV and PVFV was found (p < 0.05 for each). The decrease in PVFV was 11.7% in day 4 and 24.4% in day 8. In two patients, symptomatic hypotensive attack occured, In addition, serum potasium levels were increased significantly (p was < 0.05). Nevertheless, none of these side effects led to the withdrawal of the drug. Conclusion: Short-term valsartan treatment significantly decreases the portal blood flow in cirrhotic patients without causing serious side effects. However, long-term effects of angiotensin II receptor antagonists are controversial and studies elucidating this are warranted.
Efectos a corto plazo del valsartán sobre el flujo sanguíneo portal en pacientes con cirrosis
Keywords: alanine aminotransferase; albumin; angiotensin 2 receptor antagonist; aspartate aminotransferase; beta adrenergic receptor blocking agent; losartan; M protein; potassium; propranolol; saralasin; sodium; valsartan; adult; aged; artery diameter; article; blood flow velocity; blood volume; cardiovascular effect; color ultrasound flowmetry; drug effect; drug withdrawal; female; hemodynamics; high risk patient; human; hyperkalemia; hypotension; liver blood flow; liver cirrhosis; major clinical study; male; portal vein blood flow; potassium blood level; pulsatile flow; side effect; superior mesenteric artery